Change Factors in the Process of Cognitive‐Behavioural Therapy for Obsessive–Compulsive Disorder. (3rd October 2016) - Schwartz, C.; Hilbert, S.; Schubert, C.; Schlegl, S.; Freyer, T.; Löwe, B.; Osen, B.; Voderholzer, U.
Abstract : While there is a plethora of evidence for the efficacy of cognitive‐behavioural therapy (CBT) in obsessive–compulsive disorder (OCD), studies on change factors of the therapeutic process that account for this success are scarce. In the present study, 155 participants with primary OCD were investigated during CBT inpatient treatment. The Yale–Brown Obsessive–Compulsive Scale‐SR served as a measure of symptom severity. In addition, the following process change factors were measured: therapeutic relationship, experience of self‐esteem during therapy, experience of mastery, problem actualization and clarification. All variables were assessed on a weekly basis for seven weeks. Linear mixed growth curve analyses were conducted to model the decrease of symptoms over time and to analyse whether the change factors predicted symptom reduction. The analyses revealed a linear decrease of symptoms with high inter‐individual variation. Results further showed that increase in self‐esteem and mastery experiences as well as the initial score on mastery experience and clarification predicted decrease on the Y‐BOCS. We conclude that CBT therapists should focus on clarification in the very first sessions, and try to boost self‐esteem and self‐efficacy, which is related to mastery, throughout the treatment of OCD. Copyright © 2016 John Wiley & Sons, Ltd. Key Practitioner Message: Increase in mastery and self‐esteem experiences are associated with symptom decrease in obsessive–compulsive disorder (OCD) during cognitive‐behavioural therapy (CBT). Initial score of mastery experiences and problem clarification predict symptom decrease in OCD during CBT. CBT therapists should focus on problem clarification in the very first sessions and try to boost self‐esteem and self‐efficacy throughout the treatment of OCD.